Who helps the unemployed? Workers' receipt of public and private transfers - Kathryn Anne Edwards (IZA Journal of Labor Economics, 2020)
I use longitudinal data from the Panel Study of Income Dynamics (PSID) to measure the extent to which an unemployment spell increases the likelihood that a worker receives a cash transfer from family. I examine the prevalence of cash transfers from family, the demographic distribution of unemployed receivers, and the variation between family supported and not family supported spells. I further investigate how this informal, private assistance relates to public transfers from Unemployment Insurance using state-by-year variation in the UI program. I find that unemployment increases the probability a worker receives financial assistance from their family, inclusive of all demographic subgroups, that family cash transfer receipt is growing over time, and is weakly related to UI availability.
Keywords: J65; D64; J15; 330; Unemployment; unemployment insurance; transfers; racial inequality